Engaging community pharmacy in tuberculosis case detection (ENHANCE): a study protocol for an implementation study in Indonesia - Ivan Surya Pradipta; Carla Florencia; Cut Ainul Mardhiyyah; Firda Shafira Nurfadila; Kevin Aprilio; Rizky Abdulah; Bony Wiem Lestari; Rovina Ruslami; Trisasi Lestari; Rob Aarnoutse (Archives of Public Health)
Abstract Introduction A significant number of possible tuberculosis (TB) missing cases are still reported globally. Pharmacies are reported as a significant first point of contact for people with TB. Unfortunately, the practice of TB detection in pharmacies is still lacking. Therefore, this study aims to implement and evaluate a community pharmacy program for TB case finding in a systematic and structural approach. Methods An implementation study will be piloted in Bandung City, Indonesia, from February to November 2025. The program will engage pharmacy personnel in screening, educating, and referring people with presumed TB to community health centers (CHCs) for further diagnostic work-up. This study will involve selecting 20 pharmacies and 4 CHCs. Sequential research activities will be performed, incorporating quantitative and qualitative approaches, i.e., (1) building a coalition, (2) developing a conceptual program, (3) program socialization and educational intervention, and (4) program implementation and evaluation. The program outcomes will be reached according to the sequential research activities: (1) a joint agreement among the key actors and implementers, (2) a conceptual program for implementation, (3) improved capacity of implementers and availability of practice aids and system for the implementation, (4) the effectiveness of the program implementation. The Consolidated Framework for Implementation Research will be used as a framework in this study. Descriptive and multivariable analyses will be used for quantitative data, while thematic analysis will be used for qualitative data. Finally, an implementation outcome will be comprehensively analyzed, considering the quantitative and qualitative data analyses for the key factors of the successful program.